Globalization and its Implications for the Field of Education in Indonesia: Between Challenge and Response - Subandowo, M; Suwirta, Andi (SOSIOHUMANIKA, 2014)
ABSTRACT: The process of globalization is now entering almost all aspects of human life. The process of globalization is due to the acceleration of innovation and its application in science and technology. All phenomena of globalization have had the implications in the field of education, including the education system in Indonesia. In the context of the teaching-learning process, for example, it seems to have been and will being changing, in pertaining with the development of science and information technology, that is emergencing of an e-learning phenomenon (learning through electronic media) and the application of multi-media technology in the learning process. Therefore, education in Indonesia must be ready to welcome the phenomena of globalization with all its challenges and responses. Indeed, the education sector in Indonesia is still a "cinderella" (step child) in the process of nation building. Institute for R & D (Research and Development) is also still being accessories and not yet functioning optimally. It is appropriate if the Indonesia government and society to change the paradigm and to reorient about the critical role of education as a vehicle, not only to educate and advance the nation-state but also to improve the quality of the HR (Human Resources) that are creative and innovative, have a work ethic and high morale, and able to stand up right in order parallel to the other nation-states in the world.KEY WORD: Globalization, science and technology, education, economic development, human resources, creative and innovative, and work ethic.Â RESUME: âGlobalisasi dan Implikasinya bagi Dunia Pendidikan di Indonesia: Antara Tantangan dan Jawabanâ. Proses globalisasi saat ini sudah memasuki hampir seluruh aspek kehidupan manusia. Proses globalisasi ini terjadi akibat akselerasi inovasi dan penerapannya di bidang sains dan teknologi. Semua fenomena globalisasi itu berimplikasi dalam bidang pendidikan, termasuk sistem pendidikan di Indonesia. Dalam konteks proses belajar-mengajar, misalnya, nampaknya telah dan akan mengalami perubahan, sekaitan dengan perkembangan sains dan teknologi informasi, yaitu munculnya fenomema e-learning (belajar melalui media elektronik) dan aplikasi teknologi multi media dalam proses belajar. Karenanya, dunia pendidikan di Indonesia harus siap menyambut fenomena globalisasi ini dengan segala tantangan dan jawabannya. Memang, sektor pendidikan di Indonesia masih menjadi âcinderellaâ (anak tiri) dalam proses pembangunan bangsa. Lembaga LITBANG (Penelitian dan Pengembangan) pula masih bersifat asesoris dan belum berfungsi secara optimal. Sudah selayaknya jika pemerintah dan masyarakat Indonesia mengubah paradigma dan melakukan reorientasi tentang sentralnya peran pendidikan sebagai wahana, selain untuk mencerdaskan dan memajukan bangsa juga untuk meningkatkan kualitas SDM (Sumber Daya Manusia) yang kreatif dan inovatif, punya etos kerja dan semangat juang yang tinggi, serta mampu tegak berdiri, sejajar dengan bangsa-bangsa lain di dunia.KATA KUNCI: Globalisasi, sains dan teknologi, pendidikan, pembangunan ekonomi, sumber daya manusia, kreatif dan inovatif, serta etos kerja.Â Â About the Authors: Dr. M. Subandowo is a Senior Lecturer at the Postgraduate Program UNIPA (University of PGRI Adibuana) in Surabaya, East Java; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Department of History Education, Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. Corresponding author is: atriwusidna@gmail.comHow to cite this article? Subandowo, M. & Andi Suwirta. (2014). âGlobalization and its Implications for the Field of Education in Indonesia: Between Challenge and Responseâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7(2) November, pp.293-300. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112.Chronicle of the article: Accepted (October 9, 2014); Revised (November 10, 2014); and Published (November 20, 2014).